Factors Influencing School Development and Student Enrollment: A Case Study of Santa Maria 1 Senior High School, Cirebon - Indrawati, Natalia Tika; Suwarno, Henky Lisan (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study analyses the internal and external factors influencing school development and student enrollment at Santa Maria 1 Senior High School, Cirebon. Student numbers have fluctuated in the past five years, showing the need for institutional improvement. This research adopts a qualitative method, applying the Root Cause Analysis (RCA) technique to identify the root of the problem and formulate appropriate development strategies. The data for this study were obtained through in-depth interviews with various stakeholders, including the foundation, principal, teachers, students, alumni, and parents. The results of this study indicate that school development and the increasing number of students are influenced by a combination of internal factors such as the quality of education program, leadership system, facilities, and the school image, as well as external factors that covered the economic conditions of the community, public perception, and competition with other schools. The root cause includes a lack of innovation in learning programs, promotion strategies were insufficient, and the misalignment of school values with community expectations. This study suggests the need for increased innovative learning programs, maximizing the strategic digital promotion, strengthening the school image, and involvement from active stakeholders to raise the competitiveness and the number of students sustainably.